EVALUASI SIMPANGAN STRUKTUR AKIBAT PENAMBAHAN LANTAI DENGAN METODE ANALISIS STATIK DAN DINAMIK RESPONSE SPECTRUM (Studi Kasus : Pembangunan Gedung Dekanat Fakultas Teknik UNTIRTA) - Soelarso, Soelarso; Baehaki, Baehaki (JURNAL SPEKTRAN; Vol 5 No 2 (2017): Vol. 5, No. 2, Juli 2017, 2017)
The Advancement of Science and Technology made Indonesians increasingly concerned about education at the university so that the increasing of students must be balanced with the development of education building infrastructure. In 2015, have been built 3 floors which functioned as offices for Dean Faculty of Engineering Untirta, but in the process of implementation is done re-design with the addition of 3 floors above it to meet space requirement at the Faculty of Engineering Untirta. This research was conducted to re-analyze the deflection of structure building in order to know the deflection of structures due to the addition of load and the effect of earthquake force, so that can be evaluated to plan the addition of floor as much as 3 floors in Faculty of Engineering Untirta building structure. The analytical method used are the equivalent static analysis and dynamic response spectrum analysis using the computer program Extended Three dimensional Analysis Building System (ETABS). Resulted from 3D model analysis with the addition of 3 floors, the behavior of structures in the modes 1,2 and 3 respectively happened translations X direction, Y direction and Z axis rotation. Base shear force that occurred for 1.549.45 kN at X direction and 1.581,06 kN at Y direction. Maximum deflection that happened at 298,65 mm due to earthquake load X direction, 249,59 mm due to earthquake load Y direction. The deflection value has exceeded the allowable deflection limit of 186 mm, so that the existing structures cannot resist against the working load  due to the addition of the floor according to the design standard of SNI 03-1726-2012.